2000
DOI: 10.1097/00006454-200006000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of transmission of hepatitis C to babies of human immunodeficiency virus-negative women: the role of breast-feeding in transmission

Abstract: The presence of transitory viremia without seroconversion indicates that the vertical transmission of HCV is not important. This could be related to the viral charge and ingestion of milk of HCV-RNA-positive mothers. However, to advise avoidance of maternal breast feeding, it would be necessary to conduct larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
17

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 25 publications
1
52
0
17
Order By: Relevance
“…The fact that children are more likely to clear HCV infections than adults is supported by the finding that only 8 of 33 children sampled in years 2 and/or 3 continued to be HCV-RNA positive (32). The 76% (25 of 33) HCV clearance rate was much greater than the 23% clearance rate among the children in the EPHN multicenter project (29).…”
Section: Mother-to-infant Transmission For Hcvmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that children are more likely to clear HCV infections than adults is supported by the finding that only 8 of 33 children sampled in years 2 and/or 3 continued to be HCV-RNA positive (32). The 76% (25 of 33) HCV clearance rate was much greater than the 23% clearance rate among the children in the EPHN multicenter project (29).…”
Section: Mother-to-infant Transmission For Hcvmentioning
confidence: 99%
“…Ceci et al (31) conducted a 2-year follow-up of 60 HCV-infected infants born to HCV-RNA-positive mothers and reported that 75% cleared their infections. RuizExtremera et al (32) reported that 7 of 8 Spanish infants born to anti-HCV-positive mothers followed for an average of 29 months had detectable HCV-RNA and anti-HCV, both of which cleared. Others reported that 2 of 3 infants with perinatal HCV cleared their viremia by 2 months of age (33).…”
Section: Mother-to-infant Transmission For Hcvmentioning
confidence: 99%
“…Although mother-to-infant transmission occurred across a wide range of maternal viral titers, in 9 studies statistically higher maternal viral titers corresponded to a greater tendency for mother-to-infant transmission 19,33,34,40,[42][43][44][45][46] ; in 9 studies there was no difference. 18,20,27,[35][36][37][38][39]41 Most studies reported mother-to-infant transmission at viral titers beyond the range of 10 5 to 10 6 copies/mL.…”
Section: Maternal Viral Titermentioning
confidence: 99%
“…[24][25][26][27]31,34,35,38,40,48 Only one of these studies defined the extent (duration and exclusivity) of breast feeding. 24 Overall rates of mother-to-infant transmission between breast-fed and non-breast-fed infants were similar.…”
Section: Breast Feedingmentioning
confidence: 99%
“…18,50 Nevertheless, breast-feeding is generally not considered to be a risk factor for mother-to-infant transmission of HCV. 8,44,51,52 In published studies, the rate of transmission is nearly identical in breast-or bottle-fed infants.…”
Section: Breast-feeding and Transmission Of Hepatitis Cmentioning
confidence: 99%